PENYULUHAN TENTANG GANGGUAN MENSTRUASI DI DESA MEUNASAH INTAN KECAMATAN KRUNG BARONA JAYA KABUPATEN ACEH BESAR - Muharrina, Cut Rahmi; Martina, Martina; Marjunita; Nurlaila; Zulbaini, Andgela; Amalia, Shinta; Hastuti, Dewi (Transpublika Publisher, 2021)
Menstrual disorders vary, including pain, heavy bleeding, and no menstruation. Actually, there are many other disorders, but these three types of menstrual disorders that often occur, therefore this article will only discuss these three things. Menstruation is the process of bleeding that occurs periodically and periodically due to the shedding of the lining of the inner uterine wall (endometrium) on the uterine wall that comes out through the vagina in the form of blood vessels, glands and cells that are not used due to the absence of fertilization or pregnancy. Menstruation is a normal periodic bleeding of the uterus which is a physiological function that occurs in female primates. Basically, menstruation is a catabolic process and occurs under the influence of pituitary and ovarian hormones. Menstruation occurs at the age of adolescent girls for the first time varies between 10-16 years, but the average is 12.5 years and lasts until menopause (usually occurs around the age of 45-55 years). The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge of menstrual disorders, namely 29 (74,4%) in the good category. The conclusion is that there is a significant increase in respondents’ knowledge after being given counseling.